Pinch-off mechanism in double-lateral-gate junctionless transistors fabricated by scanning probe microscope based lithography - Larki, Farhad (Beilstein-Institut, 2012)
A double-lateral-gate p-type junctionless transistor is fabricated on a low-doped (10(15)) silicon-on-insulator wafer by a lithography technique based on scanning probe microscopy and two steps of wet chemical etching. The experimental transfer characteristics are obtained and compared with the numerical characteristics of the device. The simulation results are used to investigate the pinch-off mechanism, from the flat band to the off state. The study is based on the variation of the carrier density and the electric-field components. The device is a pinch-off transistor, which is normally in the on state and is driven into the off state by the application of a positive gate voltage. We demonstrate that the depletion starts from the bottom corner of the channel facing the gates and expands toward the center and top of the channel. Redistribution of the carriers due to the electric field emanating from the gates creates an electric field perpendicular to the current, toward the bottom of the channel, which provides the electrostatic squeezing of the current.